Explosive boiling of water films based on molecular dynamics simulations: Effects of film thickness and substrate temperature. (5th February 2023) - Ilic, Milica; Stevanovic, Vladimir D.; Milivojevic, Sanja; Petrovic, Milan M.
Highlights: Explosive boiling onset depends on film thickness and substrate temperature. Thermal and mechanical effects are significant for explosive boiling triggering. Thermally caused explosive boiling is related to approaching spinodal temperature. Mechanical effects are related to pressure wave propagation and tensile stresses. Tensile stresses cause film stretching and increase of per atom potential energy. Abstract: This paper deals with investigations of mechanisms governing explosive boiling of water films on hot copper substrate with plain surface. The investigations are based on results of molecular dynamics (MD) simulations in which film thickness (7.5 nm, 17 nm and 25.5 nm) and substrate temperature (800 K, 700 K and 600 K) are set as parameters. Analyses of heating transients, which lead to explosive boiling event, are done comparing the following quantities for considered MD configurations: time instant of explosive boiling onset, dynamics of vapour generation, increase of water film thickness due to thermal expansion and vapour generation, evolution of water temperature as well as heat transfer from the copper substrate to the water film. These analyses have shown that explosive boiling onset is related neither to the value of substrate temperature nor to the film thickness in a straightforward way. The investigations of temperature and per atom energy in the water region near the heating substrate surface have revealed that beside thermal also mechanical mechanisms can play significant role in triggering of explosive boiling. The mechanical mechanisms, related to pressure wave propagation in liquid film, comprise occurrence of tensile stresses which induce / intensify generation of vapour phase in the near wall region. The obtained results show that thermal effects are dominant in cases with high substrate temperature and thick liquid films as in these configurations the water temperature reaches spinodal value and explosive boiling is triggered before expansion wave reaches the near wall region. In cases when water in the near wall region is strongly overheated (but well below spinodal temperature), tensile stresses induced by expansive wave propagation cause intensive vapour generation and contribute dominantly to occurrence of explosive boiling. Finally, in cases with lower substrate temperature and thin liquid films, an interplay of thermal and mechanical mechanisms leads to explosive boiling. Beside these, the disjoining pressure seems to play a role in cases with thin liquid films.